The Implementation of The Medina Charter Values in Preventing Religious and Global Humanitarian Tensions - Khair, Abdul; Adawiyah, Rabiatul; Mualimin, Mualimin (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2024)
This study aims to explore why the values of the Medina Charter (Piagam Madinah) have begun to be abandoned by major world powers, resulting in disruptions to global peace and the persistence of conflicts, such as those between Israel and Hamas, Myanmar and the Rohingya ethnic group, as well as the Syrian civil war, which has claimed numerous lives. The data collection method involved systematic procedures through a literature review. The findings reveal that the reasons for the abandonment of the Medina Charter stem from political and social factors. Politically, countries such as the United Kingdom and the United States support Israel as a gesture of gratitude, as these nations received assistance from Jewish individuals during World Wars I and II. Additionally, human rights violations, a social factor, manifest in forms such as discrimination, as seen in Myanmar against the Rohingya ethnic group. Also, the civil war in Syria was caused by political and social factors.